Risperidone alone or in combination for acute mania. - Rendell, J; Gijsman, H; Bauer, MS; Goodwin, G; Geddes, G (2006)
BACKGROUND: Risperidone, an atypical antipsychotic, is used to treat mania both alone and in combination with other medicines. OBJECTIVES: To review the efficacy and tolerability of risperidone as treatment for mania. SEARCH STRATEGY: The Cochrane Collaboration Depression, Anxiety and Neurosis Controlled Trials Register (CCDANCTR-Studies December 2004), The Cochrane Central Register of Controlled Trials (CENTRAL), EMBASE, MEDLINE, CINAHL and PsycINFO were searched in December 2004. Reference lists and English language textbooks were searched; researchers in the field and Janssen-Cilag were contacted. SELECTION CRITERIA: Randomised controlled trials comparing risperidone with placebo or other drugs in acute manic or mixed episodes. DATA COLLECTION AND ANALYSIS: Two reviewers independently extracted data from trial reports. Janssen-Cilag was asked to provide missing information. QUALITY ASSESSMENT: As in other trials of treatment for mania, the high proportion of imputed efficacy data resulting from rates of failure to complete treatment of between 12% and 62% may have biased the results. MAIN RESULTS: Six trials (1343 participants) of risperidone as monotherapy or as adjunctive treatment to lithium, or an anticonvulsant, were identified. Permitted doses were consistent with those recommended by the manufacturers of Haldol (haloperidol) and Risperdal (risperidone) for treatment of mania and trials involving haloperidol allowed antiparkinsonian treatment. Risperidone monotherapy was more effective than placebo in reducing manic symptoms, using the Young Mania Rating Scale (YMRS) (weighted mean difference (WMD) -5.75, 95% confidence interval (CI) -7.46 to -4.04, P<0.00001; 2 trials) and in leading to response, remission and sustained remission. Effect sizes for monotherapy and adjunctive treatment comparisons were similar. Low levels of baseline depression precluded reliable assessment of efficacy for treatment of depressive symptoms. Risperidone as monotherapy and as adjunctive treatment was more acceptable than placebo, with lower incidence of failure to complete treatment (RR 0.66, 95% CI 0.52 to 0.82, P = 0.0003; 5 trials). Overall risperidone caused more weight gain, extrapyramidal disorder, sedation and increase in prolactin level than placebo. There was no evidence of a difference in efficacy between risperidone and haloperidol either as monotherapy or as adjunctive treatment. The acceptability of risperidone and haloperidol in incidence of failure to complete treatment was comparable. Overall risperidone caused more weight gain than haloperidol but less extrapyramidal disorder and comparable sedation. AUTHORS' CONCLUSIONS: Risperidone, as monotherapy and adjunctive treatment, is effective in reducing manic symptoms. The main adverse effects are weight gain, extrapyramidal effects and sedation. Risperidone is comparable in efficacy to haloperidol. Higher quality trials are required to provide more reliable and precise estimates of its costs and benefits.